Caracterización y diagnóstico de amenazas ambientales de la Microcuenca de la quebrada Gualagchuco, en el periodo 2021- 2022. - Reyes Guanoquiza, Robinson Fernando (2022)
The watershed is a system of catchment and concentration of surface water in which natural resources and human settlements interact within a complex set of relationships. Effluent contamination is a prevalent problem nowadays, and adequate water resources management is necessary. The main objective of this research was to diagnose the environmental threats of the Gualagchuco Creek micro-watershed (MQG). Topographic, geological, climatic, and socioeconomic parameters were used for the biophysical and socioeconomic characterization of the MQG, information collected from the National Institute of Meteorology and Hydrology (INAMHI), Ministry of Environment, Water and Ecological Transition (MAATE), National Risk and Emergency Management Service (SNGRE), National Institute of Statistics and Census (INEC), Ministry of Education of Ecuador (MINEDUC), Ministry of Public Health (MSP) and Ministry of Agriculture and Livestock (MAG), and the Development and Land Use Plan (PDOT) of the Pelileo canton. The diagnosis of the MQG shows a state of vulnerability; the main problem is due to intensive agriculture, which has caused the overuse of soils and erosion in the area. Followed by the textile industry, which has generated contamination problems in water quality criteria for human consumption and domestic use, water quality criteria for agricultural or irrigation use, water quality criteria for livestock use, and general standards for effluent discharge into freshwater bodies. The parameters for iron (2.73 mg/l), manganese (0.34 mg/l), 5-day biochemical oxygen demand (BOD5) (<13 mg/l), chemical oxygen demand (COD) (<20 mg/l), nitrates (8.92 mg/l), dissolved oxygen (6.49 mg/l), surfactants (3, 97 mg/l), total nitrogen (90.5 mg/l), ammoniacal nitrogen (76.8 mg/l), total suspended solids (424 mg/l) and fecal coliforms (160000 nmp/100 ml) exceed the maximum permissible limits (MPL) established in Ministerial Agreement 097ª. Then, this shows contamination of the water resource, which generates a proliferation of bad odors and turbid watersheds. The water is unsuitable for agricultural use, domestic consumption, preservation of aquatic life, and discharges into the freshwater body; therefore, greater control and monitoring of productive activities in the Creek Micro-Watershed is needed.